Synthesis of oligoarylacetylenes with defined conjugated sequences using tailor-made soluble polymer supports. Issue 59 (7th July 2017) - Szweda, Roza; Chendo, Christophe; Charles, Laurence; Baxter, Paul N. W.; Lutz, Jean-François
Abstract : The use of polystyrene-based soluble polymer supports greatly simplifies the synthesis and characterization of self-aggregating sequence-defined oligoarylacetylenes. Abstract : Due to their strong tendency to self-aggregate, unfunctionalized oligoarylacetylenes are difficult to synthesize. Here, tailored polystyrene soluble supports, prepared by atom transfer radical polymerization and post-polymerization modification, were tested for preparing sequence-defined oligoarylacetylenes. Controlled aromatic sequences were obtained by iterative Sonogarisha coupling, using phenyl- and pyridine-based building-blocks.